1997
DOI: 10.1152/ajpendo.1997.273.4.e801
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of pp120 on insulin endocytosis by two variant insulin receptor isoforms

Abstract: The insulin receptor is expressed as two variably spliced isoforms that differ by the absence (isoform A) or presence (isoform B) of a 12-amino acid sequence encoded by exon 11 at the carboxy terminus of the α-subunit. Coexpression of the A isoform and pp120, a substrate of the insulin receptor tyrosine kinase, in NIH 3T3 fibroblasts increased receptor A-mediated insulin endocytosis and degradation by two- to threefold compared with cells expressing receptors alone. Because B is the predominant isoform in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…Nonetheless, they persist in the fusion pellet independently of the phosphorylation state of pp120, suggesting that they may not be significant components of the internalization complex. DISCUSSION We have reported previously that co-expression of fulllength, not truncated, pp120 in NIH 3T3 cells increased receptor-mediated insulin endocytosis and degradation compared with cells expressing insulin receptors alone (11,12). In the current studies, we observed that pp120 regulated receptormediated insulin endocytosis by taking part in a complex of proteins required for insulin endocytosis.…”
Section: Fig 2 Indirect Immunofluorescence Pp120 Does Not Undergo supporting
confidence: 62%
See 1 more Smart Citation
“…Nonetheless, they persist in the fusion pellet independently of the phosphorylation state of pp120, suggesting that they may not be significant components of the internalization complex. DISCUSSION We have reported previously that co-expression of fulllength, not truncated, pp120 in NIH 3T3 cells increased receptor-mediated insulin endocytosis and degradation compared with cells expressing insulin receptors alone (11,12). In the current studies, we observed that pp120 regulated receptormediated insulin endocytosis by taking part in a complex of proteins required for insulin endocytosis.…”
Section: Fig 2 Indirect Immunofluorescence Pp120 Does Not Undergo supporting
confidence: 62%
“…Moreover, receptor-mediated insulin endocytosis and degradation were 2-3-fold higher in NIH 3T3 cells co-expressing fulllength pp120 than in cells expressing insulin receptors alone. More recently, we have reported that full-length pp120 stimulated insulin endocytosis via high affinity (receptor-A) rather than low affinity (receptor-B) insulin receptors, despite being equally phosphorylated by both isoforms (12). This suggests that pp120-induced increase in insulin endocytosis and degradation does not depend on its phosphorylation state.…”
mentioning
confidence: 86%
“…Confluent cells were lysed in 1% Triton X-100 lysis buffer supplemented with protease inhibitors (7) prior to analysis by SDS-PAGE and immunoblotting with α-CC1, as described previously (21). Screening for expression of EGFRs was achieved by measurement of EGF binding in intact cells, as described previously (7,26).…”
Section: Methodsmentioning
confidence: 99%
“…It exerts this effect by undergoing internalization as part of the receptor-mediated insulin endocytosis complex and increasing its cellular uptake via clathrin-coated vesicles (25)(26)(27)(28). Transgenic mice with liver-specific overexpression of the phosphorylation-defective S503A CEACAM1-4L mutant (L-SACC1) develop impaired insulin clearance, hyperinsulinemia, insulin resistance, and increased visceral obesity (9).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin Binding and Internalization-Primary hepatocytes, isolated as described previously (5), were grown for 24 h prior to [ 125 I]insulin (10 pM) binding at 4°C (30). Unbound insulin was removed, and cells were incubated at 37°C for 0 -60 min before incubating in 0.1% bovine serum albumin/phosphate-buffered saline (pH 3.5) for 10 min.…”
Section: Methodsmentioning
confidence: 99%